INNOVATIVE DEVELOPMENT OF AGRICULTURE (International Conference on Modern Science and Scientific Studies, 2025)
The paper examines the features of innovation processes in agriculture. The implementation of innovative projects should become a priority area for the development of agriculture. The introduction of innovative technologies in agriculture is the only effective scenario for the development of this industry.